Determining Correlation Between Males from Different y-Chromosomal Lineages and their Susceptibility Resistance to Prostate Cancer Using Multiple Dys and Binary Markers - Nargesi, Mirsaed Miri (2011)
Prostate cancer is a major health burden throughout the world. It is proposed that a complex genetics influences on prostate cancer and a similarity in genetic elements may affect the susceptibility or resistance of men to this disease. Since the geographical specificity of haplogroups implies that males from different ethnic groups have various Y-lineages with different Y-chromosomal haracteristics, using of Y-chromosomal markers (such as DYS and Binary markers) might be a powerful tool to investigate the susceptibility or resistance of men to prostate cancer. In this study, four Y-linked polymorphic microsatellite markers including DYS388, DYS435, DYS437, and DYS439, and 10 Y-linked binary markers including M20, M35, M96, M120, M172, M201, M207, M217, M231, and M258 were examined to classify Malaysian and Iranian prostate cancer patients and normal control males residing in both countries. The study group included a total of 373 subjects comprising 84 samples from Malaysian prostate cancer patients (36 Malays, 44 Chinese, and 4 Indians), 91 samples from Malaysian healthy control group (40 Malaysian-Malays, 47 Malaysian- Chinese, and 4 Malaysian-Indians), 98 samples from Iranian prostate cancer patients,and 100 samples from Iranian healthy control group. The peripheral blood was collected from all participants for genomic DNA extraction. For DYS markers, a multiplex PCR was optimized to co-amplify four above mentioned DYS loci in a single reaction tube. All DNA samples were genotyped for alleles of four DYS loci using a Genetic Analysis System CEQ8000 (Beckman Coulter). Also, an Allele Specific PCR method was optimized for every above mentioned Y-linked binary loci. In this study,alleles 12 (D) of DYS388 [(Iranians: OR, 3.242; 95% CI, 1.808 – 5.815; P < 0.01) (Malaysians: OR, 3.587; 95% CI, 1.847 – 6.966; P < 0.01) (Malaysian-Malays: OR,2.714; 95% CI, 1.022 – 7.209; P = 0.042) (Malaysian Chinese: OR, 6.006; 95% CI,2.231 – 16.171; P < 0.01) (whole study population: OR, 3.314; 95% CI, 2.147 – 5.116;P < 0.01)] and allele 14 of DYS439 [(Malaysians: P = 0.018 for Malaysians)(Malaysian-Malays: P = 0.030) (whole study population: OR, 8.736; 95% CI, 1.082 – 70.552; P = 0.015)] were significantly associated with a higher risk to develop prostate cancer. On the other hand, allele 10 (B) [(Malaysians: OR, 0.129; 95% CI, 0.047 – 0.357; P < 0.01) (Malaysian Malays: OR, 0.176; 95% CI, 0.036 – 0.870; P = 0.02)(Malaysian Chinese: OR, 0.070; 95% CI, 0.015 – 0.325; P < 0.01) (whole study population: OR, 0.152; 95% CI, 0.057 – 0.400; P < 0.01)] and 13 (E) of DYS388 [(Iranians: OR, 0.219; 95% CI, 0.09 – 0.533; P < 0.01) (whole study population: OR,0.430; 95% CI, 0.221 – 0.838; P = 0.011) were significantly associated with the lower risk of developing prostate cancer. These findings support the hypothesis that males from different Y-chromosomal origins are different regarding their susceptibility or resistance to prostate cancer. Also, A total of 76 different haplotypes comprising different alleles of four DYS loci were found among the whole study samples, of which haplotypes DABB (Iranians: OR, 7.615; 95% CI, 0.919 – 63.099; P = 0.028), DABD (Iranians: P = 0.022), DAAB [(Malaysian: P = 0.035) (whole study population: OR, 2.862; 95% CI, 0.999 – 8.195; P = 0.042)], DABC (Malaysian-Chinese: P = 0.035),and DAAC (whole study population: OR, 2.134; 95% CI, 0.998 – 4.563; P = 0.046)showed a higher frequency among patients than healthy controls, while haplotypes BABD [(Malaysian: OR, 7.615; 95% CI, 0.042 – 0.930; P = 0.024) (Malaysian-Chinese: OR, 0.201; 95% CI, 0.043 – 0.931; P = 0.024) (whole study populations: OR, 0.201; 95% CI, 0.043 – 0.931; P = 0.024)] and DAAF (whole study population: P =0.021) had a lower frequency among patient than controls. Therefore, it is likely that men who belong to the lineages with DAAB, DABC, DABD, or DABB haplotypes have a higher risk to develop prostate cancer, while those belonging to lineages with either BABD or DAAF haplotypes are less exposed to this disease than other males.However, the evidences do not strongly support the hypothesis regarding the association of DYS haplotypes with the risk of prostate cancer. The comparison between frequencies of 10 haplogroups studied in this research showed no significant differences between prostate cancer patient and healthy control groups in all populations studied. In conclusion, results of this study emphasize the influence of genetic elements on prostate cancer and some alleles of DYS388 and less likely DYS439 as well as some DYS haplotypes have the potential to be used as a screening method for prediction of susceptibility to prostate cancer both in Malaysian and Iranian populations.